Risk factors for COVID-19 infection in people with 4th dose of bivalent mRNA vaccines in general medicine from October 2022 to February 2023 - Jose Luis Turabian (Archives of Community Medicine and Public Health - Peertechz Publications, 2023)
Background: Risk factors of COVID-19 infection in people vaccinated with the 4th dose of mRNA COVID-19 vaccine remain the subject of debate. Objective: To identify risk and protective factors of COVID-19 in vaccinated people with 4th dose of bivalent mRNA vaccines. Location: General Practitioner consultation in Toledo (Spain). Methodology: Longitudinal and prospective study of cases and controls of adult patients with or without COVID-19 infection in vaccinated people with 4th dose of bivalent mRNA vaccines, from October 1, 2022, to February 28, 2023. Results: Five cases of COVID-19 infections in vaccinated people with 4th dose were included, which were compared with 52 controls (with 4th dose and without COVID-19 after the booster). The risk factors for COVID-19 infection with the 4th dose were: Women (RR = 1.67), Socio-Health Care Workers (RR = 10.39; p = 0.0349), Chronic Diseases of the blood (RR = 6.9. p = 0.0322), Chronic Diseases of Endocrine (RR = 2.72. p = 0.039425), and Chronic Diseases of Circulatory system (RR = 1.87). Conclusion: In the general practice setting in Toledo, Spain, being a socio-health care worker and having chronic diseases presumably associated with immunosuppression were statistically significant risk factors for COVID-19 infection in people vaccinated with the 4th dose of bivalent mRNA vaccines. The most exposed or immunosuppressed people continue to be at risk of becoming infected with SARS-CoV-2 despite having received the 4th dose of the mRNA COVID-19 vaccine, so other preventive methods in these groups are advisable.